2010
DOI: 10.1001/jama.2010.534
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Adjuvant Chemotherapy for Resectable Gastric Cancer

Abstract: Among the RCTs included, postoperative adjuvant chemotherapy based on fluorouracil regimens was associated with reduced risk of death in gastric cancer compared with surgery alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
223
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 690 publications
(234 citation statements)
references
References 51 publications
6
223
0
5
Order By: Relevance
“…Adjuvant chemotherapy is currently regarded as the standard protocol for patients with stage II or III gastric cancer based on National Comprehensive Cancer Network guidelines23, 24. However, the criteria for selection of candidates who are likely to benefit from adjuvant chemotherapy remain controversial2, 24.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant chemotherapy is currently regarded as the standard protocol for patients with stage II or III gastric cancer based on National Comprehensive Cancer Network guidelines23, 24. However, the criteria for selection of candidates who are likely to benefit from adjuvant chemotherapy remain controversial2, 24.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the CLASSIC study reported a higher 5year OS in patients with stage II or III gastric cancer who received adjuvant chemotherapy treatment with capecitabine plus oxaliplatin compared to patients who underwent only D2 gastrectomy (5year OS rate: 78% vs 69%; HR = 0.58, 95%CI: 0.470.72, P < 0.0001) [15] . Finally, a metaanalysis by the Global Advanced/ Adjuvant Stomach Tumor RESEARCH International Collaboration (GASTRIC) Group that combined data from 3838 patients (17 trials) showed a benefit of 5-FUbased adjuvant chemotherapy vs surgery alone on OS (55.3% vs 49.6%, respectively; HR = 0.82, 95%CI: 0.760.90, P < 0.001) with stable results at 10 years (48% vs 40%, respectively) [16] . For this reason, 5FU based adjuvant chemotherapy is now considered as a therapeutic option and has been included in the French National Thesaurus of Digestive Oncology (www.snfge.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%
“…Recently, a metaanalysis showed that addition of an anthracycline to the CDDP and 5FU regimens increased the OS of patients with advanced disease, but this Samalin E et al . Neoadjuvant therapy for gastroesophageal adenocarcinoma advantage was not reported in the GASTRIC meta analysis that combined data from 3226 patients [16,28] . A recently published French trial (FNCLCC 94012 FFCD 9703) evaluated another perioperative (two neoadjuvant cycles and four postoperative cycles) chemotherapy regimen (continuous protracted intra venous infusion of 5FU 800 mg/m² per day from days 1 to 4 and 100 mg/m² CDDP on day 1 or 2 every 4 wk) [29] .…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…It seems that this regimen might be an alternative to the S-1 regimen. A meta-analysis on 17 trials of adjuvant chemotherapy after gastrectomy showed a small but significant benefit for 5-FU-based chemotherapy [66] . Adjuvant chemotherapy increased OS by 6%, and reduced the risk of death by 18%.…”
Section: Adjuvant Chemotherapymentioning
confidence: 99%